2005
DOI: 10.1055/s-2005-918602
|View full text |Cite
|
Sign up to set email alerts
|

Fahrsimulatoruntersuchung bei Patienten mit obstruktivem Schlafapnoe-Syndrom: Konsequenzen für die Beurteilung der Fahrtüchtigkeit?

Abstract: In OSA-patients improvement of daytime performance in a simulated driving situation can be documented 14 days after initiation of CPAP. There is need for investigating larger cohorts of patients so that current recommendations for driving licensing can be modified and permission to drive can be given earlier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
0
3
0
5
Order By: Relevance
“…It took three months for the OSA subjects to reach the same ESS scores as comparisons and while their FOSQ scores steadily improved over the study period, they never achieved the same level as the comparison group. Studies in which objective measures of sleepiness are repeatedly assessed have reported improvements within the first few days following initiation of PAP, which plateau within two to six-weeks [9, 10]. Less is known about the time-course of change in subjective measures over an extended period as most previous studies have only compared two endpoints –before and one to three-months after starting PAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It took three months for the OSA subjects to reach the same ESS scores as comparisons and while their FOSQ scores steadily improved over the study period, they never achieved the same level as the comparison group. Studies in which objective measures of sleepiness are repeatedly assessed have reported improvements within the first few days following initiation of PAP, which plateau within two to six-weeks [9, 10]. Less is known about the time-course of change in subjective measures over an extended period as most previous studies have only compared two endpoints –before and one to three-months after starting PAP.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of sleep assessment is another potential factor. Sleepiness has been shown to improve within two weeks using MSLT [9] and driving simulator outcomes [10], while subjective improvement occurs more slowly [11, 12]. Finally, the nature of the residual symptoms may depend on how it is perceived by the patient; many complain of persistent fatigue, inattention or lack of a sense of well-being rather than “sleepiness” per se [13].…”
Section: Introductionmentioning
confidence: 99%
“…Insbesondere für die OSA wurde auch mit unterschiedlichen Fahrsimulatoren eine signifikant höhere Unfallrate in der simulierten Fahrsituation gegenüber Gesunden sowie eine deutliche Absenkung der Unfallhäufigkeit unter CPAP-Therapie nachgewiesen [18,20,21].…”
Section: Unfallhäufigkeit Bei Osa Unter Therapieunclassified
“…Es sollte nach Ablauf dieser Frist zur Überprüfung der Therapiecompliance und neuropsychologischer Testergebnisse eine Nachuntersuchung erfolgen (Rühle et al 1998). Neuere Studienergebnisse (Orth et al 2005b) belegen, dass der Therapieerfolg schon nach kürze-rer Frist (14 Tage) nachgewiesen werden kann, was unter wirtschaftlichen Aspekten wichtig ist (sechswöchige Krankschreibung fast nicht möglich). Bei privaten Kraftfahrern sollten die Aufmerksamkeitsfunktionen alle zwölf Monate, bei Berufskraftfahrern alle sechs Monate kontrolliert werden (Rühle et al 1998).…”
Section: Fahrtauglichkeitunclassified